2016
DOI: 10.1002/phar.1806
|View full text |Cite
|
Sign up to set email alerts
|

Remimazolam: Pharmacologic Considerations and Clinical Role in Anesthesiology

Abstract: Midazolam, fentanyl, and propofol are commonly used for sedation in modern anesthesia practice. These agents possess characteristics that have afforded various anesthetics to be delivered and produce relatively safe and effective outcomes. However, each agent has certain drawbacks in clinical practice. Remimazolam, a novel benzodiazepine created out of so-called soft drug development, is an ultrashort-acting intravenous sedative-hypnotic currently being investigated in clinical trials. In this review, we evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
120
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(126 citation statements)
references
References 27 publications
0
120
0
Order By: Relevance
“…22,23 With such structural modifications, remimazolam is extensively metabolized by plasma and tissue esterases, thereby resulting in an ultraeshort-acting sedative effect profile. 2 These properties make remimazolam a potential candidate to replace propofol and midazolam in procedural anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 With such structural modifications, remimazolam is extensively metabolized by plasma and tissue esterases, thereby resulting in an ultraeshort-acting sedative effect profile. 2 These properties make remimazolam a potential candidate to replace propofol and midazolam in procedural anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…If only intended for providing preoperative anxiolysis and not added as medication for maintaining the anesthetic, a reliably performing, shorter acting anxiolytic could be a more suiting companion for this purpose. If preferring a benzodiazepine, remimazolam may in the future be an interesting option [9]. …”
Section: Discussionmentioning
confidence: 99%
“…[ 4 , 20 ] Propofol, the most widely used sedative drug for its rapid onset and offset, can induce sedation by acting on γ-aminobutyric acid subtype A (GABA A ) receptors in the central nervous system and other tissues. [ 21 ] However, due to its adverse effects such as cardiorespiratory depression, a professional anesthetist is required to monitor the patient's vital signs during the operation. In the studies reported by Hoogland et al, [ 11 , 20 ] intravenous analgesia with opioid medication and midazolam sedation were used to enhance the effect of local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] But it shows significant disadvantages regarding to time of onset and offset. [ 21 ] Interestingly, a Cochrane review found that there was low-quality evidence that intravenous midazolam administered before a procedure reduced anxiety when compared with placebo. [ 23 ] Therefore, further studies are needed to evaluate the effect of intraoperative administration of sedative drugs in PTED surgery.…”
Section: Discussionmentioning
confidence: 99%